Effects and differences of various concentration techniques on the evolution of therapeutic components in Lushan geothermal water - Bo Zhang; Zheng Fang; Keng Xuan; Wenjie Ma; Bai Gao; Yuanyuan Liu; Dandan Huang; Silei Xie; Yan Ding (Scientific Reports)
Abstract Hot springs are significant geothermal resources characterized by their high mineral content and therapeutic value. This study aims to preserve the therapeutic element value of the Lushan hot springs in Jiangxi, China. Laboratory batch experiments, microstructural characterization, and hydrogeochemical modeling were employed to investigate the effects and differences of various concentration techniques under different environmental parameters on the evolution of therapeutic components in hot spring water. The key findings are as follows: Fluoride (F) concentrations in the hot spring water, along with elevated levels of iron (Fe) and manganese (Mn) observed at sampling point S2, exceed the World Health Organization (WHO) drinking water quality standards. Among the tested methods, atmospheric evaporation at 100 °C and pH = 4 demonstrated the highest concentration efficiency. Although freeze concentration achieved its best performance under − 8 °C and pH = 6, its overall efficiency was still lower than that of atmospheric evaporation. However, freeze concentration requires low energy consumption and short processing cycles, making it a promising research direction for future hot spring concentration techniques.The evolution of potentially toxic elements revealed that arsenic (As) concentrations decreased during freeze concentration and remained below standard values at a freezing rate of 93.75%. In contrast, concentrations of chromium (Cr), manganese (Mn), and lead (Pb) exceeded permissible limits during atmospheric evaporation.SEM-EDS results showed differences in the microstructure of solid precipitates obtained from the two concentration methods. XPS analysis indicated that freeze concentration led to greater precipitation of potassium (K) and calcium (Ca) compared to atmospheric evaporation.PHREEQC simulations demonstrated that therapeutic components such as fluoride (F), lithium (Li), and strontium (Sr) primarily existed as single ions under both concentration methods, while silicon (Si) predominantly occurred as soluble SiO2.This study provides green, diversified, and value-enhancing technological support for the sustainable development of geothermal resources in Lushan.